Shi-shi-etko ebook - Campbell, Nicola (2019)
Winner of the Anskohk Aboriginal Children's Book of the Year Award. Finalist for the TD Canadian Children's Literature Award, the Marilyn Baillie Picture Book Award and the Ruth Schwartz Award In just four days young Shi-shi-etko will have to leave her family and all that she knows to attend residential school. She spends her last days at home treasuring the beauty of her world — the dancing sunlight, the tall grass, each shiny rock, the tadpoles in the creek, her grandfather's paddle song. Her mother, father and grandmother, each in turn, share valuable teachings that they want her to remember. And so Shi-shi-etko carefully gathers her memories for safekeeping. Richly hued illustrations complement this gently moving and poetic account of a child who finds solace all around her, even though she is on the verge of great loss — a loss that Indigenous Peoples have endured for generations because of the residential schools system. Correlates to the Common Core State Standards in English Language Arts: CCSS.ELA-LITERACY.RL.K.1 With prompting and support, ask and answer questions about key details in a text. CCSS.ELA-LITERACY.RL.1.3 Describe characters, settings, and major events in a story, using key details. CCSS.ELA-LITERACY.RL.1.7 Use illustrations and details in a story to describe its characters, setting, or events. CCSS.ELA-LITERACY.RL.2.5 Describe the overall structure of a story, including describing how the beginning introduces the story and the ending concludes the action.